Hydrogen storage investigation of fixed bed of nano-crystalline Mg-Ni-Cr mixed oxides - Abdus Salam, M (2013)
Nano-crystalline mixed oxides containing magnesium, nickel and chromium (MNCM) have been synthesized as an adsorbent using coprecipitation method and showed its reversible hydrogen storage capacity at ambient conditions using fixed bed. XRD and ICP-MS analyses ensured the adsorbent’s phase and homogeneity. The microstructure of mixed oxide has been investigated using FESEM and BET and TEM technique respectively. The adsorbent consisted of mesoporous surface with a surface area of 254-370 m2gm-1 and SAED pattern showed that the adsorbents are poly-crystalline. The mixed oxides exhibited a 3.2 wt% H2 storage capacity and release 57% of adsorbed H2. Adsorption enthalpy (ΔH) and entropy (ΔS) change of -27.58 kJ/mol and -70.21 J/mol.K are indicating favorable thermodynamics for reversible hydrogen storage material.